2003
DOI: 10.21273/hortsci.38.7.1337
|View full text |Cite
|
Sign up to set email alerts
|

Remontant Flowering Potential of Ten Hydrangea macrophylla (Thunb.) Ser. Cultivars

Abstract: Floral induction of 10 Hydrangea macrophylla (Thunb.) Ser. cultivars (`All Summer Beauty', `Dooley', `Endless Summer', `Générale Vicomtesse de Vibraye', `Lilacina', `Mariesii Variegata', `Mme. Emile Mouillère', `Nikko Blue', `Penny Mac', and `Veitchii') was evaluated to determine the remontant flowering potential. Cultivars exhibiting superior flowering potential could facilitate year-round production of florist s hydrangea and expand the geographic adaptation of hydrangea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Flow cytometry analysis indicated that 'Lady in Red' and Midnight Duchess Ò are diploids, but the H. angustipetala plant has a larger genome size, indicative of a higher ploidy level (data not presented). All plants were grown outdoors under 45% shadecloth in 11.36-L containers filled with an amended pine bark substrate (Adkins and Dirr, 2003) and were overhead-irrigated as necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry analysis indicated that 'Lady in Red' and Midnight Duchess Ò are diploids, but the H. angustipetala plant has a larger genome size, indicative of a higher ploidy level (data not presented). All plants were grown outdoors under 45% shadecloth in 11.36-L containers filled with an amended pine bark substrate (Adkins and Dirr, 2003) and were overhead-irrigated as necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Sepal coloration, inflorescence type, and the timing of flower bud initiation are the most important flowering traits in hydrangea. While flower color changes in hydrangea have been shown to be a result of internal detoxification of Al under low-pH conditions 5 , inflorescence type and the timing of flower bud initiation are largely under genetic control [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Remontancy is a highly desired trait for modern landscape plants, as consumers consistently choose varieties with season-long floral display and reliable blooming in more northerly or frost-prone areas 11 . Well-known remontant H. macrophylla cultivars, include "All Summer Beauty", "Bailmer" (marketed as "Endless Summer" ® ), "David Ramsey", "Decatur Blue" "Early Sensation" (marketed as "Forever and Ever" ® ), "Oakhill", and "Penny Mac" 6,7,9 . New remontant cultivars are often introduced as collections within an established brand, such as the Endless Summer ® series, Forever & Ever ® series, and Let's Dance ® series.…”
Section: Introductionmentioning
confidence: 99%
“…It ends with floral maturity, the growth of inflorescence axes, and the onset of flowering. The organogenesis of inflorescence is characterized by different development stages (Adkins and Dirr, 2003;Litlere and Stromme, 1975). These stages were defined to measure the effect of growing conditions on floral development and to allow us to obtain highquality horticultural plants.…”
mentioning
confidence: 99%